Lessons from case studies of integrating mental health into primary health care in South Africa and Uganda - Bhana Arvin; Ssebunnya Joshua; Petersen Inge; Baillie Kim (International Journal of Mental Health Systems, 2011)
Abstract Background While decentralized and integrated primary mental healthcare forms the core of mental health policies in many low- and middle-income countries (LMICs), implementation remains a challenge. The aim of this study was to understand how the use of a common implementation framework could assist in the integration of mental health into primary healthcare in Ugandan and South African district demonstration sites. The foci and form of the services developed differed across the country sites depending on the service gaps and resources available. South Africa focused on reducing the service gap for common mental disorders and Uganda, for severe mental disorders. Method A qualitative post-intervention process evaluation using focus group and individual interviews with key stakeholders was undertaken in both sites. The emergent data was analyzed using framework analysis. Results Sensitization of district management authorities and the establishment of community collaborative multi-sectoral forums assisted in improving political will to strengthen mental health services in both countries. Task shifting using community health workers emerged as a promising strategy for improving access to services and help seeking behaviour in both countries. However, in Uganda, limited application of task shifting to identification and referral, as well as limited availability of psychotropic medication and specialist mental health personnel, resulted in a referral bottleneck. To varying degrees, community-based self-help groups showed potential for empowering service users and carers to become more self sufficient and less dependent on overstretched healthcare systems. They also showed potential for promoting social inclusion and addressing stigma, discrimination and human rights abuses of people with mental disorders in both country sites. Conclusions A common implementation framework incorporating a community collaborative multi-sectoral, task shifting and self-help approach to integrating mental health into primary healthcare holds promise for closing the treatment gap for mental disorders in LMICs at district level. However, a minimum number of mental health specialists are still required to provide supervision of non-specialists as well as specialized referral treatment services.